FDEM investigation on the crack propagation characteristics of walnut shell under multi-contact loadings - Han, Bowen; Su, Gege; Zeng, Yong; Yang, Jialong; Fan, Xiuwen; Zhang, Yongcheng; Zhang, Hong; Wang, Jianping (Frontiers in Materials, 2023)
Walnut shell breaking is an important aspect of post-harvest processing. However, shell-breaking results differ significantly from ideal uniaxial compression results. In this paper, the effect of multipoint loading on the walnut shell-breaking mechanism by combining FDEM with cohesive elements was investigated. The model for walnuts was created using micro-X-ray CT scans and experimental data. Simulation parameters describing mechanical properties were calibrated through modeling the uniaxial compression experiment. The loading point locations were quantitatively described in terms of top and azimuthal angles. The results show that the crack ex-tension rate increases with the number of loading points and the singularity value, and the maximum value of the four-point loading speed is about 450 m/s. The number of cracks is only related to the number of loading points and is not related to the location of the loading point. In addition, three loading methods are proposed, and the fastest crack propagation rate is achieved when the azimuthal angle of four-point loading is 0, 150, 180, and 330, respectively. These findings may serve as a theoretical foundation for studying shell crushing.